Festival loyalty to a South African literary arts festival: action speaks louder than words!. Issue 2 (18th September 2019) - Kruger, Martinette
Abstract : Purpose: The purpose of this paper is to fill the gap in the literature by focusing on the profile and loyalty of visitors to a literary arts festival in South Africa. In addition, this research advocates that festivals can influence visitors' supplementary behavioural intentions and actions beyond loyalty in the form of literary arts appreciation, purchases and tourism. Design/methodology/approach: A visitor survey was conducted at one of the oldest literary arts festivals in the country where a total of 391 completed self-administered questionnaires were obtained. The statistical analyses comprised three factor analyses (motives to attend the festival, satisfaction with the festival offering elements and behavioural intentions) as well as structural equation modelling, to establish the relationship between the motives, evaluation of the "festivalscapes", behavioural intentions and loyalty. Findings: The findings confirmed that literary arts festival loyalty is the principle behavioural intention that will occur after attending a literary arts festival. However, the results demonstrated that literary arts festivals also have the potential to increase and stimulate supplementary behavioural intentions in the form of greater awareness of the arts, increased purchasing behaviour of literary works, increased travel to support the literary arts and greater personal involvement. Practical implications: Festivals, irrespective of the art form that they showcase, therefore, play a significant role in encouraging and increasing purchasing behaviour, which is vital to the viability and continuation of the arts industry. Originality/value: This is one of the first studies to research the literary arts festival market in South Africa, thereby making a distinct contribution by expanding the literature on the needs of this neglected market and the aspects that influence loyalty to these types of festivals.